Novel Recruitment Methods for Research Among Young Adults in Rural Areas Who Use Opioids: Cookouts, Coupons, and Community-Based Staff. (November 2020) - Young, April M.; Ballard, April M.; Cooper, Hannah L.F.
Objectives: Rural communities in the United States are increasingly becoming epicenters of substance use and related harms. However, best practices for recruiting rural people who use drugs (PWUD) for epidemiologic research are unknown, because such strategies were developed in cities. This study explores the feasibility of web- and community-based strategies to recruit rural, young adult PWUD into epidemiologic research. Materials and Methods: We recruited PWUD from rural Kentucky to participate in a web-based survey about opioid use using web-based peer referral and community-based strategies, including cookouts, flyers, street outreach, and invitations to PWUD enrolled in a concurrent substance use study. Staff members labeled recruitment materials with unique codes to enable tracking. We assessed eligibility and fraud through online eligibility screening and a fraud detection algorithm, respectively. Eligibility criteria included being aged 18-35, recently using opioids to get high, and residing in the study area. Results: Recruitment yielded 410 complete screening entries, of which 234 were eligible and 151 provided complete, nonfraudulent surveys (ie, surveys that passed a fraud-detection algorithm designed to identify duplicate, nonlocal, and/or bot-generated entries). Cookouts and subsequent web-based peer referrals accounted for the highest proportion of screening entries (37.1%, n = 152), but only 29.6% (n = 45) of entries from cookouts and subsequent web-based peer referrals resulted in eligible, nonfraudulent surveys. Recruitment and subsequent web-based peer referral from the concurrent study yielded the second most screening entries (27.8%, n = 114), 77.2% (n = 88) of which resulted in valid surveys. Other recruitment strategies combined to yield 35.1% (n = 144) of screening entries and 11.9% (n = 18) of valid surveys. Conclusions: Web-based methods need to be complemented by context-tailored, street-outreach activities to recruit rural PWUD.